Comparative analysis of connective tissue disease-associated interstitial lung disease and idiopathic pulmonary fibrosis from a tertiary care centre in Pakistan - Ali Bin Sarwar Zubairi; Huzaifa Ahmad; Maryam Hassan; Faraz Siddiqui; Nousheen Iqbal; Mehmood Riaz; Muhammad Irfan (Journal of the Pakistan Medical Association, 2021)
Objectives: The burden of interstitial lung disease (ILD) is rising globally. This study aimed to describe and compare characteristics of Connective Tissue Disease-associated ILD with Idiopathic Pulmonary Fibrosis, the two most commonly observed ILDs among outpatients at a tertiary care hospital in Karachi, Pakistan. Methods: A retrospective research study was conducted. Patients with ILD were identified through the outpatient data registry at the Aga Khan University Hospital (AKUH), Karachi from October 2016 to October 2017. We obtained data pertaining to demographics, clinical and radiologic features. A comparative analysis was done to compare the patient characteristics and key features between CTD-ILD and IPF patients. The analysis was done using STATA version 12.0. Results: We identified 184 patients with ILD, which included 52 (29.3%) with CTD-ILD and 62 (35%) with IPF. The most prevalent conditions among CTD-ILD patients included rheumatoid arthritis (42.3%) and scleroderma (25%). Usual interstitial pneumonitis was the common radiologic pattern in RA-ILD (63.6%) and scleroderma (61.5%) while non-specific interstitial pneumonitis was more common in MCTD (85.7%) and SLE (80%). Compared to patients with IPF, those with CTD-ILD were predominantly younger (p<0.001) and female (88.5 % v 45.2%, p<0.001). History of GERD was also significantly lower in CTD-ILD (p=0.05). Conclusion: CTD-ILD patients in our registry were younger and predominantly female compared to IPF. Further studies and ongoing data registry are needed to understand the full spectrum of this disease and long term clinical outcomes. Keywords: Connective tissue disease, Interstitial lung disease, Idiopathic pulmonary fibrosis. Continuous...